FENOMENA KOMUNIKASI REMAJA PEREMPUAN BERTATO DI PEKANBARU - Adhitya Nugraha; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Tattooing is a form of expression of someone who poured through the medium of the body and has a meaning for their owners. the phenomenon of tattoos among women has begun implicated. This is due to a shift in lifestyle that mimics the habit in a big city. Tattooed women in Pekanbaru assume that the tattoo is part of the appreciation of the art form. Most teenage girls with tattoos have a habit of hanging out with friends of the opposite sex until late at night, drinking alcohol, and smoking. Although not all the girls who do it but their behavior gets skewed responses from the public.This type of research uses qualitative method with phenomenological approach. Determination of research subjects and informants using purposive sampling considerations. Activity data collection can be done to no more than ten people informant. Criteria informants in this study were: (1) The informant are young women aged 18 -21 years of age or student and student who tattooed his body. (2) The informant is a citizen pekanbaru. While the object of this research is a phenomenon that appears as experienced by women tattooed in Pekanbaru. Data collection techniques in this research was conducted through observation, interviews, documentation and internet searching. Technical analysis of the data used in this study is a qualitative analysis and be open (open-ended), inductive. The technique of testing the validity of the data using the extension of participation and triangulation.The results of this study indicate the motives of women who have a tattoo is to express themselves, describe something that they love through tattoos. The shape of the tattoo drawn on their bodies is an artistic symbol that represents their motive tattooed on their bodies. The response from the public towards women with tattoos lead to negative stigma and assume women are tattooed wild woman.Keyword : Phenomena, Communications, Youth, tattoos